A Comparison of Labour Standards in the United States and Canada - Block, Richard; Roberts, Karen (Relations industrielles / Industrial Relations, 2000)
This article introduces a methodology for measuring differences in the labour standards between the United States and Canada, taking into account variations by state and province. This methodology is then used to analyze differences in the two countries on ten labour standards. The results indicate that six standards are higher in Canada than in the United States: paid time off, unemployment/employment Insurance, workers' compensation, collective bargaining, unjust discharge and advance notice of plant closings/large scale layoffs. Standards covering minimum wages, overtime and occupational safety and health are higher in the United States than in Canada. There is no difference in the two countries in standards covering employment discrimination/employment equity. The results suggest that overall, although there are exceptions, labour standards are higher in Canada than the United States.